A multicentre, randomised, double-blind, placebo-controlled trial with the interleukin-1 receptor antagonist anakinra in patients with systemic-onset juvenile idiopathic arthritis (ANAJIS trial). Issue 5 (20th December 2010) - Quartier, Pierre; Allantaz, Florence; Cimaz, Rolando; Pillet, Pascal; Messiaen, Claude; Bardin, Christophe; Bossuyt, Xavier; Boutten, Anne; Bienvenu, Jacques; Duquesne, Agnes; Richer, Olivier; Chaussabel, Damien; et al.
Abstract : Objectives: To assess the efficacy of the interleukin 1 receptor antagonist anakinra in systemic-onset juvenile idiopathic arthritis (SJIA). Methods: A multicentre, randomised, double-blind, placebo-controlled trial was conducted. The primary objective was to compare the efficacy of a 1-month treatment with anakinra (2 mg/kg subcutaneous daily, maximum 100 mg) with a placebo between two groups each with 12 patients with SJIA. Response was defined by a 30% improvement of the paediatric American College of Rheumatology criteria for JIA, resolution of systemic symptoms and a decrease of at least 50% of both C-reactive protein and erythrocyte sedimentation rate compared with baseline. After month 1 (M1), patients taking placebo were switched to anakinra. Secondary objectives included tolerance and efficacy assessment for 12 months, and analyses of treatment effect on blood gene expression profiling. Results: At M1, 8/12 responders were receiving anakinra and 1 responder receiving placebo (p=0.003). Ten patients from the placebo group switched to anakinra; nine were responders at M2. Between M1 and M12, six patients stopped treatment owing to an adverse event (n=2), lack of efficacy (n=2) or a disease flare (n=2). Blood gene expression profiling at enrolment and at 6 months' follow-up showed one set of dysregulated genes that reverted to normal values in the clinical responders and a different set, including interferon (IFN)-inducible genes, that was induced by anakinra. Conclusions: Anakinra treatment is effective in SJIA, at least in the short term. It is associated with normalisation of blood gene expression profiles in clinical responders and induces a de novo IFN signature. Trial Registration Number: NCT00339157 .